Revestimento de gomas do cajueiro e gelana com extratos de plantas para aplicação em barra de fruta - Oliveira, Leilanne Marcia Nogueira (2019)
Edible coatings are developed to interact favorably with food, increasing your shelf life. In this context, the objective of this work was to develop an edible coating of cashew gums (Anacardium occidentale L.) and gill extract of leaves of chambá (Justicia pectoralis Jacq.) And black quince (Croton jacobinensis Baill.) For bar application açaí. Aqueous and hydroalcoholic extracts of chambá and black quince were obtained and characterized in terms of total phenolic compounds, total antioxidant activity and antimicrobial activity against the bacteria Escherichia coli, Listeria monocytogenes, Salmonella Enteritidis and Staphylococcus aureus. The extracts with the best antimicrobial activity were evaluated for cytotoxicity against human epithelial cells through MTT [3- (4,5-dimethylthiazol-2-yl) -2,5-diphenyl-tetrazolium bromide] and to the profile of substances by chromatography associated with mass spectrometry. An experimental design of the rotational central composite type 22 with 6 axial and 3 central points totaling 11 formulations was performed to obtain edible coatings based on cashew and gellan gums, in which the concentrations of cashew and gycerol plasticizer were varied. These coatings were characterized for color, rheology, zeta potential and contact angle. The most promising incorporated formulation of the extract with the best antimicrobial potential was applied to açaí bars stored at 5 ° C for 30 days. The bioaccessibility of the total phenolic compounds and the total antioxidant activity of the coated and uncoated bars was determined. The results showed that the highest amounts of total phenolic compounds and higher total antioxidant activities were found in the ethanolic extract of 70% for both plants studied. All the plant materials presented activity against the strains of bacteria tested, being the aqueous extracts of chambá and hydroalcoholic 70% of black quince, the most efficient ones. The extracts showed no toxicity by the MTT method. The most promising formulation of the coating was the treatment with gum solution of 11.5% cashew and 3.5% glycerol, because among other characteristics, it presented less wettability and greater spreading, through the measurement of the contact angle. The formulation was incorporated the hydroalcoholic extract 70% of black quince, which presented better antimicrobial activity, being applied in açaí bars. From the physical-chemical parameters analyzed, only significant interactions (p ≤ 0.05) between the formulations and the storage time were observed for analysis of susceptibility to syneresis, total phenolic compounds and color parameter a *. Microbiological analyzes showed that the coated açaí bars presented higher counts of mesophilic and psicrófilas bacteria and molds and yeasts. Regarding bioaccessibility, there was no significant difference between the coated and non-coated bars. The data set show the extracts of J. pectoralis Jacq. and C. jacobinensis Baill. potential candidates for use in the development of new food products. However, its incorporation into coatings needs to be further studied. The biological activity of the coating was not proven, but it avoided the syneresis of the açaí bar.